CNS and thorax Injury and associated risks factors in equestrian sports - Crawford, A. E.; Picken, L. K.; Gabriel, F. D.; Quade, J.; Gould, S. (Sports Health: A Multidisciplinary Approach, 2025)
Context: Equestrian sports continue to gain popularity in the United States and are associated with a high injury rate, especially involving the central nervous system and thorax. Due to this high rate of injury and the potential for long-term consequences associated with participation, an understanding of the unique risks of this sport is needed.